GIANT ARACHNOID CYST WITH SPONTANEOUS SHRINKING: A CASE REPORT - Ziya Asan (MNJ (Malang Neurology Journal), 2023)
Arachnoid cysts occur in approximately 1% of all intracranial space-occupying lesions and do not require a very high rate of surgical intervention. Arachnoid cysts are cystic formations containing cerebrospinal fluid. It is argued that the enlargement of the arachnoid cysts increases in volume with the unilateral valve mechanism. They are generally considered static formations because they do not tend to grow. A 16-year-old male patient was evaluated for headache attacks resistant to medical treatment. A giant arachnoid cyst located in the left temporal region was detected in the cranial MRI examination of the patient who had no history of head trauma or cranial operation in his medical history. In the MRI examination two years later, it was seen that the arachnoid cyst had almost completely disappeared. However, it was also found that it caused cambering in the temporal bone in the adjacent region. This finding supports that not all arachnoid cysts are static formations; they may have their internal dynamics and even cause shape changes in the surrounding tissues and even the cranium.